A computational theory of exchange: Willingness to pay, willingness to accept and the endowment effect - Pete Lunn; Mary Lunn (The Economic and Social Research Institute (ESRI), 2009)
We present a theory of exchange that provides an alternative explanation for the endowment effect. Unlike standard neoclassical theories and Prospect Theory, our approach is not based on preference structure, but on adaptive responses to the problem of exchange when value is uncertain. We combine assumptions from perceptual and economic theory into a highly generalised model. Agents who maximise surplus but perceive uncertainty in the value of goods, set willingness to accept (WTA) above willingness to pay (WTP). The disparity increases with the perceived uncertainty of value. We show also how feedback over repeated exchanges may have heuristic value in learning to set optimal WTA and WTP. Our model receives some support from empirical studies of exchange.
Keywords: 330; endowment effect; willingness to accept; willingness to pay; exchange; uncertainty; Tausch; Willingness to pay; Entscheidung bei Unsicherheit; Präferenztheorie; Austauschtheorie (Soziologie)